Social dimension of eastward enlargement of the eurozone - Achim Kemmerling (Free University Berlin, Jean Monnet Centre of Excellence, 2003)
This report discusses both the reshaping of certain policy areas and the socio-political repercussions an Eastward enlargement of the euro-zone may have. The focus lies on the potential for social conflict enhanced by the enlargement process and their consequences for national policy-making. The paper first surveys some of the major socio-economic changes to be expected in the course of enlarging the euro-zone. This allows to isolate the sensitive segments and areas in which enlargement will arguably lead to costs of adjustment. Next the paper discusses the political economy of major issues concerning national welfare states. It is shown that, whereas capital and goods markets are already in the process of reshaping,there is substantive political resistance against the flexibilisation of labour markets and social policies. This has implications for both national wage bargaining systems and national net contributions to the EU public budget. Two most significant projections are that the Stability and Growth Pact will be put under increasing pressure, since politicians will fear the negative consequences of fiscal retrenchment, and that CEEC will manage to double their share of EU transfers once they join EU and EMU. Finally, the report addresses 'soft issues' such as public opinion on the adoption of the Euro. The analysis of micro-data shows that although support is primarily driven by national legacies, welfare state institutions may well play a role in cushioning the short-term costs of Ezoneplus.
Keywords: D6; H0; J0; F4; E6; 330; labour market; social policies; welfare economics; EU-enlargement; EU-budget costs